2010
DOI: 10.1109/jstars.2010.2086436
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the ALOS PALSAR L-Band Backscatter—Above Ground Biomass Relationship Queensland, Australia: Impacts of Surface Moisture Condition and Vegetation Structure

Abstract: Focusing on woody vegetation in Queensland, Australia, the study aimed to establish whether the relationship between Advanced Land Observing Satellite (ALOS) Phased Array L-band SAR (PALSAR) HH and HV backscattering coefficients and above ground biomass (AGB) was consistent within and between structural formations (forests, woodlands and open woodlands, including scrub). Across these formations, 2781 plot-based measurements (from 1139 sites) of tree diameters by species were collated, from which AGB was estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
164
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 229 publications
(174 citation statements)
references
References 60 publications
8
164
0
2
Order By: Relevance
“…The study found that these processes are necessary and must be done on any SAR images before further analyses are carried out. Studies [9,11,33] have demonstrated that PALSAR polarization data actually has a logarithmic relationship with AGB. Therefore, instead of employing linear regression only, the study also attempted to correlate the AGB with the polarizations in a non-linear form.…”
Section: Satellite Datasetsmentioning
confidence: 99%
“…The study found that these processes are necessary and must be done on any SAR images before further analyses are carried out. Studies [9,11,33] have demonstrated that PALSAR polarization data actually has a logarithmic relationship with AGB. Therefore, instead of employing linear regression only, the study also attempted to correlate the AGB with the polarizations in a non-linear form.…”
Section: Satellite Datasetsmentioning
confidence: 99%
“…It is a site-specific factor and difficult to obtain in practice, therefore it is set to 1 [19,32,33,73].…”
Section: Alos/palsar Processingmentioning
confidence: 99%
“…A number of approaches have been proposed, and different results have been obtained with different model parameters, such as vegetation cover and soil surface roughness [9][10][11]. These roughness and vegetation contribution from the retrieval procedure.…”
Section: Introductionmentioning
confidence: 99%